Risk Factor of Depression among Diabetes Mellitus Type 2 Patients in Takhli Hospital Nakhon Sawan Province - Kucharoen, Chinnavatr (Journal of Preventive Medicine Association of Thailand, 2020)
The purpose of this research is to study risk factors of depression among diabetes mellitus type 2 patients who visited the outpatient department of Takhli hospital. The research methodology is an unmatched case-control study. Data were collected from medical records of diabetes mellitus type 2 patients between 1 June to 31 August 2019 in the outpatient department of Takhli hospital by BMS-HOSxP and Three refer programs. The patients were classified into 2 groups, 60 patients of the case group and 192 patients of the control group (case:control=1:3). The case group was diabetes mellitus type 2 patients with depression. The control group was diabetes mellitus type 2 patients without depression. Depression diagnosed by DSM-5 criteria. The data of the study were 251 diabetes mellitus type 2 patients. The result was analyzed using the Chi-square test, T-test, and binary logistic regression. Accept P-value less more than 0.05 and 95% confidence interval. Baseline characteristics of the case group and the control group such as gender, age, weight, education level, marital status, and medical welfare are not statistically significant. Stroke in diabetes mellitus type 2 patients have a 6 times greater risk of depression than patients without stroke with statistical significance [ORadj = 6.01, 95%CI = 2.12 - 16.41, P < 0.001)]. Stroke is a risk factor for depression in diabetes mellitus type 2 patients. Our results reflecting the medical personnel to see the importance of screening for depression among Diabetes mellitus type 2 patients with stroke